Differential Influence of Imidazolium Ionic Liquid on Cellulase Kinetics in Saccharification of Cellulose and Lignocellulosic Biomass Substrate - Tantayotai, Prapakorn; Gundupalli, Marttin Paulraj; Panakkal, Elizabeth Jayex; Sriariyanun, Malinee; Rattanaporn, Kittipong; Bhattacharyya, Debraj (Applied Science and Engineering Progress, 2022)
The effect of [Emim][OAc] on Celluclast 1.5 L, Accellerase 1500, and IL-tolerant (MSL2) cellulase during the saccharification of carboxymethylcellulose (CMC), Avicel (AV), rice straw (RS) was studied in one pot process (pretreatment and saccharification). The inhibition caused by [Emim][OAc] (0.5–2.0 M) with substrate loading (20–50 mg/mL) were also evaluated. In most cases, the inhibition mode of saccharification for CMC and AV was identified to be uncompetitive inhibition when the concentration of [Emim][OAc] was higher than 0.5 M. Under the influence of 0.5 M of [Emim][OAc], the Critical Concentration of Substrate (CCS) values of the Celluclast 1.5 L and Accellerase 1500 on CMC hydrolysis were determined to be at 26.59 and 33.65 mg/mL, respectively. Also, increasing in [Emim][OAc] concentration could increase in CCS values, suggesting the positive effect of [Emim][OAc] on the improvement of enzymatic saccharification. This study provides insight into the process optimization for integration of [Emim][OAc] in one pot process of biorefinery.